(3HZjI GddHjH hZfjI GdWHjHs - (3EHQGgje GdWHjHs
(3ChdgG (B:s
(3bGd EHQGgje GdWHjH aj cJGHg HZjI GddHjH hZfjI GdWHjH(B: (3GdHGH GdKGfj aj JbSje GdeRGL(B: (3dPG cGf ehVhY GdWH HOf GdEfSGf jNJda HMSH GdeRGL, hGdeRGL jfbSe HMSH GdfhY hGdUfa hGdTNU s
(3BNQgG (B:s
(3Sf Gdfeh jfbSe Edi NeSI CbSGe, Sf GdWahdjI, hSf GdUHG, hSf GdJQYQY, hSf GdZdGejI, hSf GdaJi, hjfbSe Edi CQHYI CSGHjY, hcd CSHhY YfO EfJgGFg jMUd dg JCf eNUhU efg HHYVg s
(3GdehLhO GdHGH GdKGfj aj JbSje GdeRGLs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B39 ; (3eLdI eYgO GdeNWhWGJ (B- (3GdLRA (B5 - (3U (B271 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs